Avaliação de oponentes en confrontos de tilápia-do-Nilo: interação entre sinais químicos e visuais - Pinho Neto, Cândido Ferreira [UNESP] (2014)
During the establishment of contests between individuals of the same species, the factors usually described as mediators for access to information of the opponent are visual signals, such as size, coloration patterns and ritualized behaviors. Despite the importance of visual signals for communication in fish, other signals are important in this complex system. Considering the aquatic environment and the facilitated dispersion of chemicals released by individuals, it is presumed that chemical signaling may be involved in the assessment of opponents and the decision making before and / or during a contest. Thus, this study tested the effects of chemical signals and their integration with visual signals (size of the opponent) in aggressive behavior in contests between individuals of the species Oreochromis nilocticus (Nile Tilapia). To test this hypothesis, pairs were matched in a condition in which individuals could see each other, but there was no mechanical or chemical contact between them. For the contest, the focal fish of the pair was stimulated with chemical and visual signals from conspecifics, comprising the following conditions: chemical stimuli 1) conditioned water by a smaller conspecific, 2) same-sized 3) larger or 4) water; and visual stimuli 1) smaller opponent, 2) same-sized, or 3) larger. In the groups that viewed a smaller opponent, the different treatments did not change the aggressive behavior of focal fish. When viewing an opponent of the same size, individuals receiving chemical signals from size-matched and larger conspecifics showed a reduction in the expression of attacks when compared to the control group. And, viewing a larger opponent, the display time reduced regardless of the chemical stimulus and the number of attacks increased in the group receiving chemical signals from larger conspecifics when compared to control and smaller. The results show that the Nile Tilapia ...